A phase IIb dose-ranging study of the oral JAK inhibitor tofacitinib (CP-690,550) versus placebo in combination with background methotrexate in patients with active rheumatoid arthritis and an inadequate response to methotrexate alone - Kremer, Joel M.; Cohen, Stanley; Wilkinson, Bethanie E.; Connell, Carol A.; French, Jonathan L.; Gomez-Reino, Juan; Gruben, David; Kanik, Keith S.; Krishnaswami, Sriram; Pascual-Ramos, Virginia; Wallenstein, Gene; Zwillich, Samuel H. (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective To compare the efficacy, safety, and tolerability of 6 dosages of oral tofacitinib (CP‐690,550) with placebo for the treatment of active rheumatoid arthritis (RA) in patients receiving a stable background regimen of methotrexate (MTX) who have an inadequate response to MTX monotherapy. Methods In this 24‐week, double‐blind, phase IIb study, patients with active RA (n = 507) were randomized to receive placebo or tofacitinib (20 mg/day, 1 mg twice daily, 3 mg twice daily, 5 mg twice daily, 10 mg twice daily, or 15 mg twice daily). All patients continued to receive a stable dosage of MTX. The primary end point was the American College of Rheumatology 20% improvement criteria (ACR20) response rate at week 12. Results At week 12, ACR20 response rates for patients receiving all tofacitinib dosages ≥3 mg twice daily (52.9% for 3 mg twice daily, 50.7% for 5 mg twice daily, 58.1% for 10 mg twice daily, 56.0% for 15 mg twice daily, and 53.8% for 20 mg/day) were significantly (P ≤ 0.05) greater than those for placebo (33.3%). Improvements were sustained at week 24 for the ACR20, ACR50, and ACR70 responses, scores for the Health Assessment Questionnaire disability index, the 3‐variable Disease Activity Score in 28 joints using the C‐reactive protein level (DAS28‐CRP), and a 3‐variable DAS28‐CRP of <2.6. The most common treatment‐emergent adverse events occurring in >10% of patients in any tofacitinib group were diarrhea, upper respiratory tract infection, and headache; 21 patients (4.1%) experienced serious adverse events. Sporadic increases in transaminase levels, increases in cholesterol and serum creatinine levels, and decreases in neutrophil and hemoglobin levels were observed. Conclusion In patients with active RA in whom the response to MTX has been inadequate, the addition of tofacitinib at a dosage ≥3 mg twice daily showed sustained efficacy and a manageable safety profile over 24 weeks.